2011
DOI: 10.1007/s00411-011-0385-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in 210Po and 210Pb activity concentrations in the urine of Finnish population groups

Abstract: A study to determine activity concentrations of (210)Pb and (210)Po in the urine of certain Finnish population groups was conducted, to investigate the variation in natural background level of urinary excretion. The study participants were divided into three groups mainly based on their diet. The first group comprised recreational fishermen and the second group represented people consuming more reindeer meat than an average Finn, while people using drinking water with very high activity concentrations of (210)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the case of 210 Po, the average activity concentration was over five times higher in the residents of Lapland compared to those in southern Finland. In a recent study, Muikku et al [26] reported that the 210 Po content in urine was three times higher in reindeer herders than the control group representing the average population. However, in the case of 210 Pb, there was no difference.…”
Section: Pb and 210 Pomentioning
confidence: 95%
“…In the case of 210 Po, the average activity concentration was over five times higher in the residents of Lapland compared to those in southern Finland. In a recent study, Muikku et al [26] reported that the 210 Po content in urine was three times higher in reindeer herders than the control group representing the average population. However, in the case of 210 Pb, there was no difference.…”
Section: Pb and 210 Pomentioning
confidence: 95%
“…Human urine has a relatively complex matrix with high total dissolved solids and salt content, which needs to be pretreated to reduce matrix effects before chemical separation (Kang et al 2021 ). Muikku et al ( 2011 ) determined 210 Pb activity concentrations in urine by microwave-assisted acid digestion after adding concentrated HNO 3 and 209 Po to 90 mL of sample. The use of microwave digestion minimizes the operational time and consumption of reagents and energy (Mingote and Nogueira 2016 ).…”
Section: Sample Pretreatmentmentioning
confidence: 99%